Long non-coding RNA SNHG16 affects cell proliferation and predicts a poor prognosis in patients with colorectal cancer via sponging miR-200a-3p. Issue 5 (17th May 2019) - Li, Yanling; Lu, Ying; Chen, Yanglong
Abstract : Previous study has explored that SNHG16, a long non-coding RNA (lncRNA), mediated cell growth and proliferation. Yet, the role of SNHG16 in human colorectal cancer (CRC) still remains to be explored. Therefore, we conducted the present study to explore the functions of SNHG16 in CRC. In the present study, SNHG16 was significantly up-regulated in CRC tissues and cell lines. Gain- and loss-of-function of SNHG16 further presented that SNHG16 promoted the progression of CRC cells, including proliferation, migration, and invasion. Further, in vivo study also revealed that overexpression of SNHG16 could promote tumor growth. Bioinformatics analysis and luciferase reporter assay showed that SNHG16 was a direct target of miR-200a-3p. MiR-200a-3p was inversely correlated with SNHG16 expression in CRC tissues. In brief, the above results elucidate the important role of SNHG16 in CRC tumorigenesis, suggesting that SNHG16 might be quite vital for the diagnosis and development of CRC.